Risiko Tinggi Dislipidemia pada Remaja Obesitas: Menggali Faktor dan Implikasinya terhadap Kesehatan Kardiovaskular (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2023)
Dyslipidemia in obese adolescents is a marker of early-onset cardiovascular problems such as atherosclerosis. The purpose of this study was to identify the magnitude of the problem of dyslipidemia in obese adolescents. This study uses content analysis of literature reviews in synthesizing articles in accordance with the criteria and research objectives. This study uses Google Scholar, Pub Med using the keywords